Safety and Efficacy of Bromodomain and Extra-Terminal Inhibitors for the Treatment of Hematological Malignancies and Solid Tumors: A Systematic Study of Clinical Trials - Sun, Yanli; Han, Jie; Wang, Zhanzhao; Li, Xuening; Sun, Yanhua; Hu, Zhenbo (Frontiers in Pharmacology, 2021)
Background: The upregulated expression of BET proteins is closely associated with the occurrence and development of hematological malignancies and solid tumors. Several BET inhibitors have been developed, and some have been in phase I/II of clinical trials. Here, the safety, efficacy, and pharmacodynamics of ten BET inhibitors currently in clinical trials were evaluated. Methods: We retrieved and reviewed published reports on the clinical trials of twelve BET inhibitors including AZD5153, ABBV-075, BMS-986158, CPI-0610, GSK525762, OTX-015, PLX51107, INCB054329, INCB057643, FT-1101, CC-90010 and ODM-207 for patients with hematological malignancies and solid tumors and summarized their published target genes. Results: In the monotherapy of BET inhibitors, the most common and severe (grade ≥ 3) hematological adverse events (AEs) are thrombocytopenia, anemia, and neutropenia. The most common non-hematological syndromes are diarrhea, nausea, fatigue, dysgeusia, and decreased appetite, while the most severe AE is pneumonia. Additionally, Tmax of these BET inhibitors was between 0.5-6 hours, but the range for T1/2 varied significantly. According to published data, the rates of SD, PD, CR and PR were 27.4%, 37.6%, 3.5% and 5.7%, respectively, which is not very satisfactory. In addition to BRD4, oncogene MYC is another common target gene of these BET inhibitors. Ninety-seven signaling pathways may be regulated by BET inhibitors. Conclusions: All BET inhibitors reviewed in our study exhibited exposure-dependent thrombocytopenia, which may limit their clinical application. Moreover, further efforts are necessary to explore the optimal dosing schemes and combinations to maximize the efficacy of BET inhibitors.